Establishment of Typical Dose Reference Level (DRL) Values for Adult Patients Undergoing Computed Tomography in Three Hospitals in Brazzaville, Congo Republic - Guy Blanchard Dallou; Joël Bazoma; Clobite Bouka Biona; Saïdou Saïdou; Germain Hubert Ben-Bolie; Philippe Ondo Meye (Journal of Multidisciplinary Applied Natural Science, 2024)
The present study aimed at to establish typical dose reference level (DRL) values for adult patients undergoing computed tomography (CT) examinations in three hospitals in Brazzaville, Congo Republic. The examinations considered were head, chest, abdomen-pelvis, chest-abdomen-pelvis and lumbar spine CT scans. For each examination, the median of the distribution for the volume CT dose index (CTDIvol) and dose-length product (DLP) were determined. The median values were considered as the typical DRL values. Hypothesis testing was also carried out to statistically compare the mean values obtained for each participating CT facility. In the case of head scan, the typical values proposed in the present study in terms of CTDIvol and DLP were 15–48% and 28–60% lower than the DRL values reported in the literature, respectively. In the case of lumbar spine, the typical value determined in this study in terms of DLP was 48–70% greater than the DRL values provided in the literature. The typical values proposed for chest, abdomen-pelvis and chest-abdomen-pelvis were within the DRL values reported in the literature. It is possible that the adoption of the typical values proposed in the present study will help in reducing the dose received by adult patients undergoing CT examination in Congo Republic.